Upstream elements repress premature expression of an Aspergillus developmental regulatory gene. - Adams, T H (1990)
The Aspergillus nidulans abaA gene regulates intermediate steps in asexual reproductive development and is itself developmentally regulated. An 822-base-pair DNA fragment from the abaA 5'-flanking region is sufficient to drive developmentally appropriate expression of the Escherichia coli lacZ gene. Deletion analysis showed that this fragment contains elements that repress transcription in vegetative cells and immature conidiophores and that activate transcription later during development. A 45-base-pair region encompassing the major and minor abaA transcription initiation sites contains directly repeated sequences related to the mammalian initiator (Inr) element (S. T. Smale and D. Baltimore, Cell 57:103-113, 1989). This element or sequences in the untranslated leader were sufficient for correct transcription initiation and for measurable developmental induction. Similar elements were present at or near the initiation sites of other developmentally regulated genes. We propose that the temporal and spatial specificity of expression of these genes results from modulation of the activity of Inr elements.